An evaluation of cephalometric predictors of anterior open bite; An assessment of dental and skeletal parameters in an orthodontic population - Onyinye D Umeh; Sylvester Chegwe; Ifeoma L Utomi (Journal of Orthodontic Science, 2024)
BACKGROUND: Anterior open bite (AOB) malocclusion is one of the highly challenging malocclusions. Cephalometric radiographs have been used for the diagnosis of occlusal anomalies in the vertical and anteroposterior directions. This study aims to compare skeletal and dental features in open and non-open bite subjects to identify factors that help predict and categorize open bites in a Nigerian population. MATERIALS AND METHODS: Pretreatment cephalometric radiographs of 82 patients were recruited into this study. This study comprised 41 AOB patients and 41 (Class 1 malocclusion) patients (control group). The radiographs were obtained from the orthodontic unit, Department of Child Dental Health of the Lagos University Teaching Hospital, Idi-Araba Lagos. Cephalometric tracing and analysis of the obtained radiographs were used to identify and compare the skeletal and dental differences between the two groups. RESULTS: The mean age of the participants was 20.47 ± 8.05 years. The patients consisted of 26 (31.7%) males and 56 (68.3%) females. There was a significant difference in the open bite depth indicator (ODI) of the open bite (P value < 0.001). There was a statistically significant increase in the vertical skeletal parameters – lower facial height (LFH), total facial height (TFH), posterior facial height (PFH), Frankfort-mandibular plane angle (FMA), mandibular-maxillary angle (MMA), and gonial angle in the AOB group compared to the control group. The vertical height of the dentoalveolar segments measured was all significantly increased in the open bite group compared to the control group. CONCLUSION: The results suggest that the skeletal and dental vertical parameters, including ODI of the open bite subjects, varied compared with the non-open bite subjects in the Nigerian population studied and could be used to predict AOB tendency.